Anti-attrition liquid crystal screen optical film and preparation method thereof

By applying a 0.5-2μm thick sol gel coating on the optical diaphragm of the liquid crystal display, the friction and wear problem caused by electrostatic attraction is solved, the friction performance and service life are improved, and the optical performance is maintained, and the polymerization is solved The wear and electrostatic effect of the object optical diaphragm on the lower polarizer.

CN119119869AActive Publication Date: 2024-12-13SHENZHEN ZHIHONGTONG ELECTRONIC TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411248062.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The polymer optical diaphragm and the lower polarizer in the LCD screen are frictionally worn due to electrostatic attraction, which affects the optical imaging quality and causes economic losses. The microstructure of the polymer optical diaphragm is prone to scratch the lower polarizer, resulting in wear marks. and performance degradation.

Method used

Using sol-gel coating, the specific steps include preparing polyethylene glycol containing end alkoxysilanes, mixing methyl trimethoxysilane, aminosilane and fluorosilane and other components to form a sol-gel coating, by dipping or The spray coating method was applied on the optical diaphragm, and after drying, it formed a 0.5-2 μm thick anti-wear coating.

Benefits of technology

It significantly improves the friction performance of the optical diaphragm, prevents friction wear, extends service life, maintains optical transparency and structural integrity, while reducing electrostatic effects and friction damage, ensuring that the coating maintains wear-reducing performance during multiple frictions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119869A_ABST
    Figure CN119119869A_ABST
Patent Text Reader

Abstract

The invention provides an anti-attrition liquid crystal screen optical film and a preparation method thereof, and relates to the technical field of optical films, the preparation method comprises the following steps: dissolving polyethylene glycol and silane in toluene, adding dibutyltin dilaurate, carrying out reflux, and then carrying out vacuum pumping to extract a toluene solvent to obtain a residue which is polyethylene glycol containing alkoxy-terminated silane; the preparation method comprises the following steps: adding methyltrimethoxysilane, dimethyldimethoxysilane, amino silane, fluorosilane and polyethylene glycol containing terminal alkoxy silane into a mixed solvent of ethanol and isopropanol; adding a hydrochloric acid solution and glacial acetic acid into the solution, stirring and aging to obtain a sol-gel solution; and coating the sol-gel on the optical film, and drying to obtain the antifriction liquid crystal screen optical film. The liquid crystal screen optical film has the advantages that the electrostatic effect generated in the friction process is effectively reduced, and the anti-friction performance of the liquid crystal screen optical film on the lower polarizing plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical films, and in particular to a friction-reducing optical film for liquid crystal screens and a preparation method thereof. Background Art

[0002] Both triboelectric charging and frictional wear are common phenomena in the friction process of nature, and they can act on the surface of friction materials at the same time. During the friction process, the material will generate corresponding charges on the surface due to the different ability of surface atoms to gain or lose electrons. The electrostatic effect caused by these triboelectric charges has a wide range of applications in various fields. However, it can also have an adverse impact on people's life and production and even bring potential safety hazards. For example, triboelectric charges can cause breakdown of electronic and electrical components and frictional wear caused by static electricity adsorption. With the rapid development of the electronic and electrical industry, the hazards caused by triboelectric charging are becoming increasingly serious.

[0003] Among them, the polymer optical film in the liquid crystal display screen, which is an important component of the electronic and electrical industry, and the lower polarizer will be close or in contact with some areas due to the surface electrostatic attraction. These areas will cause friction and wear under the impact or vibration during the assembly and transportation of the liquid crystal screen components, affecting the quality of optical imaging, and causing huge economic losses to the liquid crystal display industry every year. The wear between the optical film and the polarizer caused by electrostatic adsorption is one of the problems that the liquid crystal display industry urgently needs to solve. Regulating the charge generated on the friction surface can control the generation and accumulation of friction charges, reduce the attraction between the optical film and the lower polarizer caused by electrostatic accumulation, and reduce the adsorption of tiny particles, which is an effective method to eliminate the adverse effects such as wear caused by frictional electrification. In addition, the polymer optical film in the liquid crystal display screen is usually prepared from polyacrylate polymers, and its surface has certain microstructures to achieve optical properties. These microstructures are easy to scratch the lower polarizer during the contact process with the lower polarizer of the liquid crystal screen, resulting in wear marks, thereby affecting its optical properties. Therefore, the anti-friction performance of the surface of the polymer optical film is also a problem that the liquid crystal display industry urgently needs to solve.

[0004] How to solve the above technical problems is the subject faced by the present invention. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present invention provides a wear-reducing liquid crystal screen optical film and a preparation method thereof.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: the present invention provides a wear-reducing liquid crystal screen optical film and a preparation method thereof. The wear-reducing liquid crystal screen optical film is realized by coating a sol-gel coating on the optical film. The specific sol-gel coating and the wear-reducing optical film preparation method include the following steps:

[0007] A. Preparation of polyethylene glycol containing terminal alkoxysilane:

[0008] Dissolve polyethylene glycol and silane in a molar ratio of 1:1 in toluene 10 times their mass, add 0.5% of the total mass of dibutyltin dilaurate, and reflux at 115°C for 2 hours;

[0009] The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane;

[0010] B. Preparation of sol-gel: adding methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane prepared in step A to a mixed solvent of ethanol and isopropanol;

[0011] Adding hydrochloric acid solution and glacial acetic acid to the solution, stirring the mixed solution, and then aging it at room temperature to obtain a sol-gel solution;

[0012] C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

[0013] The average molecular weight of the polyethylene glycol is 200 to 400.

[0014] The silane in step A is one or both of tetramethoxysilane and tetraethoxysilane.

[0015] The aminosilane described in step B is one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, and diethylenetriaminopropyltriethoxysilane.

[0016] The fluorosilane described in step B is one or more of perfluorooctyltriethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, and perfluorodecyltriethoxysilane.

[0017] The thickness of the gel coating is 0.5-2 μm.

[0018] The substance amount ratio of the aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane to methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane is 1:5-1:50.

[0019] The ratio of the amount of the aminosilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:20;

[0020] The ratio of the amount of the fluorosilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:20;

[0021] The substance amount ratio of the polyethylene glycol containing terminal alkoxysilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:20.

[0022] The beneficial effects of the present invention are as follows: the sol-gel system adopted in this scheme is based on fluorine-containing chain siloxane, siloxane containing amino side groups and polyethylene glycol containing terminal alkoxy silane. The synergistic effect of these three components makes the coated optical film show a significant improvement in friction performance. The fluorine-containing chain siloxane has high electronegativity and low surface energy characteristics of fluorine atoms, so that the coating surface shows excellent hydrophobicity and low friction coefficient, which not only reduces the direct contact between the liquid crystal screen optical film and the lower polarizing plate during use, but also effectively prevents friction and wear.

[0023] In this scheme, the introduction of siloxane containing amino side groups into the sol-gel can effectively counteract the friction charging phenomenon by forming an opposite charge with the siloxane containing fluorine chains during the friction process. Triboelectric charging is an important factor causing the increase in the friction coefficient between the optical film and the lower polarizing plate. By suppressing this phenomenon, the optical film exhibits more stable friction performance during use, extending the service life of the optical film.

[0024] In this solution, polyethylene glycol is a material with excellent lubricity, and its application in the present invention further enhances the anti-friction performance of the optical film. The presence of polyethylene glycol segments enables the sol-gel coating to form a lubricating film during the friction process, thereby reducing the friction coefficient of the coating surface. This lubricating effect not only reduces the possibility of friction damage, but also enables the coated optical film to maintain good optical transparency and structural integrity during long-term use.

[0025] The thickness of the sol-gel coating of the present invention is controlled between 0.5-2 μm, which not only ensures the anti-friction performance of the coating, but also does not affect the optical performance of the liquid crystal screen. The uniformity and stability of the coating are also fully guaranteed. In practical applications, the coating can withstand multiple frictions and still maintain its excellent anti-friction performance. This is of great significance for the long-term stable use of the liquid crystal screen.

[0026] The present invention not only improves the wear resistance of the LCD screen optical film through the innovative sol-gel system design, but also effectively reduces the electrostatic effect generated during the friction process, and enhances the lubricity and durability of the coating. The LCD screen optical film coated with the sol-gel coating exhibits better wear reduction performance, effectively reduces the wear of the lower polarizing plate during long-term use, prolongs the service life of the LCD screen, and does not adversely affect its optical performance. These advantages make the present invention have broad application prospects in the field of liquid crystal display technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the wear-reducing liquid crystal screen polymer optical film of the present invention.

[0028] Figure 2 This is a scanning electron microscope image of the polarizing plate under the initial liquid crystal screen of the present invention.

[0029] Figure 3 This is a scanning electron microscope image of the polarizing plate under the liquid crystal screen according to Example 1 of the present invention.

[0030] Figure 4 This is a scanning electron microscope image of the polarizing plate under the liquid crystal screen according to the second embodiment of the present invention.

[0031] Figure 5 This is a scanning electron microscope image of the polarizing plate under the liquid crystal screen of Example 3 of the present invention.

[0032] Figure 6 This is a scanning electron microscope image of the polarizing plate under the liquid crystal screen of Example 4 of the present invention.

[0033] Figure 7 This is a scanning electron microscope image of the polarizing plate under the liquid crystal screen of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0034] In order to clearly illustrate the technical features of this solution, this solution is described below through specific implementation methods.

[0035] Embodiment 1

[0036] This embodiment is a wear-reducing liquid crystal screen optical film and a preparation method thereof, comprising the following steps:

[0037] A. Preparation of polyethylene glycol containing terminal alkoxysilane:

[0038] 0.05 mol of polyethylene glycol with an average molecular weight of 200 and 0.05 mol of tetramethoxysilane were dissolved in 176 g of toluene, and 0.97 g of dibutyltin dilaurate was added, and refluxed at 115° C. for 2 h;

[0039] The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane;

[0040] B. Preparation of sol-gel: 0.1 mol methyltrimethoxysilane, 0.02 mol dimethyldimethoxysilane, 0.02 mol diethylenetriaminopropyltrimethoxysilane, 0.02 mol perfluorodecyltrimethoxysilane, and 0.02 mol polyethylene glycol containing terminal alkoxysilane were added to a mixed solvent of 1000 mL ethanol and 50 mL isopropanol;

[0041] 0.5 mL of 0.01 mol / L hydrochloric acid solution and 0.2 mL of glacial acetic acid were added to the solution. The mixed solution was stirred for 1 hour and then aged at room temperature for 7 days to obtain a sol-gel solution;

[0042] C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

[0043] The friction test of the wear-reducing LCD screen optical film and the polarizing plate under the LCD screen is carried out.

[0044] Embodiment 2

[0045] This embodiment is a wear-reducing liquid crystal screen optical film and a preparation method thereof, comprising the following steps:

[0046] A. Preparation of polyethylene glycol containing terminal alkoxysilane:

[0047] 0.05 mol of polyethylene glycol with an average molecular weight of 400 and 0.05 mol of tetramethoxysilane were dissolved in 276 g of toluene, and 1.38 g of dibutyltin dilaurate was added, and refluxed at 115° C. for 2 h;

[0048] The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane;

[0049] B. Preparation of sol-gel: 0.1 mol methyltrimethoxysilane, 0.02 mol dimethyldimethoxysilane, 0.02 mol diethylenetriaminopropyltrimethoxysilane, 0.02 mol perfluorodecyltrimethoxysilane, and 0.02 mol polyethylene glycol containing terminal alkoxysilane were added to a mixed solvent of 1000 mL ethanol and 50 mL isopropanol;

[0050] 0.5 mL of 0.01 mol / L hydrochloric acid solution and 0.2 mL of glacial acetic acid were added to the solution. The mixed solution was stirred for 1 hour and then aged at room temperature for 7 days to obtain a sol-gel solution;

[0051] C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

[0052] The friction test of the wear-reducing LCD screen optical film and the polarizing plate under the LCD screen is carried out.

[0053] Embodiment 3

[0054] This embodiment is a wear-reducing liquid crystal screen optical film and a preparation method thereof, comprising the following steps:

[0055] A. Preparation of polyethylene glycol containing terminal alkoxysilane:

[0056] 0.05 mol of polyethylene glycol with an average molecular weight of 200 and 0.05 mol of tetramethoxysilane were dissolved in 176 g of toluene, and 0.97 g of dibutyltin dilaurate was added, and refluxed at 115° C. for 2 h;

[0057] The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane;

[0058] B. Preparation of sol-gel: 0.1 mol methyltrimethoxysilane, 0.02 mol dimethyldimethoxysilane, 0.02 mol N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 0.02 mol perfluorodecyltrimethoxysilane, and 0.02 mol polyethylene glycol containing terminal alkoxysilane were added to a mixed solvent of 1000 mL ethanol and 50 mL isopropanol;

[0059] 0.5 mL of 0.01 mol / L hydrochloric acid solution and 0.2 mL of glacial acetic acid were added to the solution. The mixed solution was stirred for 1 hour and then aged at room temperature for 7 days to obtain a sol-gel solution;

[0060] C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

[0061] The friction test of the wear-reducing LCD screen optical film and the polarizing plate under the LCD screen is carried out.

[0062] Embodiment 4

[0063] This embodiment is a wear-reducing liquid crystal screen optical film and a preparation method thereof, comprising the following steps:

[0064] A. Preparation of polyethylene glycol containing terminal alkoxysilane:

[0065] 0.05 mol of polyethylene glycol with an average molecular weight of 200 and 0.05 mol of tetramethoxysilane were dissolved in 176 g of toluene, and 0.97 g of dibutyltin dilaurate was added, and refluxed at 115° C. for 2 h;

[0066] The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane;

[0067] B. Preparation of sol-gel: 0.1 mol methyltrimethoxysilane, 0.02 mol dimethyldimethoxysilane, 0.02 mol diethylenetriaminopropyltrimethoxysilane, 0.02 mol perfluorooctyltriethoxysilane, and 0.02 mol polyethylene glycol containing terminal alkoxysilane were added to a mixed solvent of 1000 mL ethanol and 50 mL isopropanol;

[0068] 0.5 mL of 0.01 mol / L hydrochloric acid solution and 0.2 mL of glacial acetic acid were added to the solution. The mixed solution was stirred for 1 hour and then aged at room temperature for 7 days to obtain a sol-gel solution;

[0069] C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

[0070] The friction test of the wear-reducing LCD screen optical film and the polarizing plate under the LCD screen is carried out.

[0071] Comparative Example 1

[0072] Comparative Example 1 is a polymer optical film in a liquid crystal display screen without coating.

[0073] The polymer optical film in the uncoated LCD display was subjected to friction test with the polarizing plate under the LCD display.

[0074] Copper foil is pasted on one side of a square LCD diaphragm and a lower polarizer of 4cm×4cm in size, and copper wire is glued on the copper foil, which constitutes two friction electrodes for triboelectric charging. The LCD diaphragm and the lower polarizer with copper foil and wire are installed on a linear motor, and the back-and-forth movement of the linear motor is used to make the diaphragm and the lower polarizer contact and separate. During the contact and separation process, the friction charge generated on the surface is induced to the copper foil, and then connected to the oscilloscope through the copper wire to obtain the voltage output of triboelectric charging. The movement frequency of the linear motor is 5Hz.

[0075] Friction coefficient and wear test method:

[0076] Cut the LCD screen into a 1cm×1cm square and fix it on the friction rod of the friction tester; cut the LCD screen lower plate into a 6cm×6cm square and fix it on the friction tester. The friction frequency is 1Hz and the applied load is 3N. Rub the LCD screen square on the lower plate for 30 cycles. Read the friction coefficient during the friction tester and use a scanning electron microscope (SEM) to detect the morphology of the scratches.

[0077] Table 1 Friction properties of different samples

[0078] sample Friction electrification voltage output / V Friction coefficient Example 1 5 0.29 Example 2 6 0.30 Example 3 9 0.36 Example 4 10 0.38 Comparative Example 1 63 0.53

[0079] The higher the triboelectric voltage, the more static electricity is generated during the friction process. Compared with the polymer optical film in the uncoated LCD display, the triboelectric voltage output of the coated LCD optical film is lower, indicating that less static electricity is generated during the friction process.

[0080] Compared with the polymer optical film in the uncoated LCD display, the coated LCD optical film has a lower coefficient of friction, indicating that it has better lubricity.

[0081] Figure 1 The scanning electron microscope photo of the prepared anti-friction liquid crystal screen film is Figure 2 It can be seen that the surface of the unworn lower polarizer of the LCD screen is smooth, and the lower polarizer of the LCD screen of Examples 1 to 4 has slight wear after friction with the wear-reducing LCD screen film, and the degree of wear is significantly lower than the wear of the lower polarizer by the untreated LCD screen film, which shows that the wear-reducing LCD screen film has good wear-reducing performance and reduces the degree of wear on the lower polarizer of the LCD screen.

[0082] Technical features not described in the present invention can be achieved through or by adopting existing technologies and will not be described in detail here. Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a wear-reducing liquid crystal screen optical film, characterized in that: The following steps are included: A. Preparation of polyethylene glycol containing terminal alkoxysilane: Dissolve polyethylene glycol and silane in a molar ratio of 1:1 in toluene 10 times their mass, add 0.5% of the total mass of dibutyltin dilaurate, and reflux at 115°C for 2 hours; The toluene solvent is extracted by vacuum, and the remainder is polyethylene glycol containing terminal alkoxysilane; B. Preparation of sol-gel: adding methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane prepared in step A to a mixed solvent of ethanol and isopropanol; Adding hydrochloric acid solution and glacial acetic acid to the solution, stirring the mixed solution, and then aging it at room temperature to obtain a sol-gel solution; C. Preparation of anti-friction liquid crystal screen optical film: coating the sol-gel on the optical film by dip coating or spray coating, and drying in an oven at 100° C. for 5 hours to obtain the anti-friction liquid crystal screen optical film.

2. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The average molecular weight of the polyethylene glycol is 200 to 400.

3. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The silane in step A is one or both of tetramethoxysilane and tetraethoxysilane.

4. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The aminosilane described in step B is one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, and diethylenetriaminopropyltriethoxysilane.

5. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The fluorosilane described in step B is one or more of perfluorooctyltriethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, and perfluorodecyltriethoxysilane.

6. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The thickness of the gel coating is 0.5-2 μm.

7. The method for preparing the wear-reducing liquid crystal screen optical film according to claim 1, characterized in that: The substance amount ratio of the aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane to methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane is 1:5-1:

50.

8. The wear-reducing liquid crystal screen optical film and the preparation method thereof according to claim 1, characterized in that: The ratio of the amount of the aminosilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:20; The ratio of the amount of the fluorosilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:20; The substance amount ratio of the polyethylene glycol containing terminal alkoxysilane to the total silane (methyltrimethoxysilane, dimethyldimethoxysilane, aminosilane, fluorosilane and polyethylene glycol containing terminal alkoxysilane) is 1:2-1:

20.

9. A friction-reducing liquid crystal screen optical film prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hardened antireflection optical film coating liquid used for flexible displays, and preparation method and applications thereof

    CN108424722A

  • Method for preparing high transmittance hydrophobic coating film for photovoltaic glass

    CN110002767A

  • Wear-resistant organopolysiloxane composition and preparation method thereof

    CN110079093A

  • Alkoxysilane / organic polymer composition for thin insulating film prodution and use thereof

    CN1257529A

  • Durable coating composition, process for producing durable, antireflective coatings, and coated articles

    US20010031811A1